2020
DOI: 10.1002/ccr3.3596
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous leukocytoclastic vasculitis secondary to COVID‐19 infection: A case report

Abstract: COVID‐19 is a novel disease that mostly affects the respiratory system but as the number of cases is rising significantly around the world, more extra‐respiratory manifestations are being reported among which are various dermatologic manifestations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…The term leukocytoclastic vasculitis (LCV) refers to the pathologic hallmark of small-vessel vasculitis, namely fragmentation of nuclei of neutrophils (leukocytoclasia, also referred to as “nuclear dust”) that compose the inflammatory infiltrate in the wall of arterioles, capillaries and postcapillary venules; associated histopathological features include extravasated red blood cells and fibrinoid necrosis of the vessel walls [ 3 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The term leukocytoclastic vasculitis (LCV) refers to the pathologic hallmark of small-vessel vasculitis, namely fragmentation of nuclei of neutrophils (leukocytoclasia, also referred to as “nuclear dust”) that compose the inflammatory infiltrate in the wall of arterioles, capillaries and postcapillary venules; associated histopathological features include extravasated red blood cells and fibrinoid necrosis of the vessel walls [ 3 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Histological features of LCV can be found in: ANCA-associated vasculitis, immune complex vasculitis, such as cryoglobulinemic vasculitis, IgA-vasculitis (Henoch–Schoenlein purpura), hypocomplementemic urticarial vasculitis (anti-C1q vasculitis) and IgM/IgG immune complex vasculitis (formerly known as hypersensitivity vasculitis), vasculitis associated with systemic diseases (e.g., rheumatoid arthritis, systemic lupus erythematosus and sarcoidosis) and vasculitis secondary to infections, medications, sepsis or cancer [ 3 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…There have been case reports of adults presenting with this entity after COVID-19 but none reported in a paediatric age group. [7][8][9] This might be mostly due to the relative low incidence rate of COVID-19 infection in children. However, asymptomatic infections in children still may cause silent vascular damage to them.…”
Section: Discussionmentioning
confidence: 99%
“…The biopsy had shown leucocytoclastic vasculitis. 8 Camprodon Gómez et al 9 reported a relatively younger 29-year-old man who presented with purple palpable papules over the lower limbs and abdomen. He had symptomatic COVID-19 infection a month prior to presentation.…”
Section: Discussionmentioning
confidence: 99%
“…Several cases of cutaneous small vessel vasculitis in COVID-19 patients have been documented, often accompanied by palpable purpura ( Dominguez-Santas et al, 2020 ; Mayor-Ibarguren et al, 2020 ; Schenker et al, 2021 ; Tahir et al, 2020 ). More specifically, leukocytoclastic vasculitis in COVID-19 patients has been observed in both children and adults ( Iraji et al, 2021 ; Kumar et al, 2021 ). Henoch-Schonlein purpura associated with COVID-19 infection has been reported ( AlGhoozi and AlKhayyat, 2021 ).…”
Section: Cutaneous Manifestations Relating To Covid-19mentioning
confidence: 99%